METHOD FOR FORECASTING THE RELIABILITY OF AN EXTERNAL PILOT OF A REMOTE PILOTED AERIAL SYSTEM - Ivanov, Oleksandr; Ivanov, Volodymyr (Proceedings of National Aviation University (archive), 2019)
The stochastic model of actions of the human operator of the ergatic system is proved. The model is based on a simple Markov circuit in the form of a unipolar signal. In it, the set of "logical zeros" corresponds to the error-free operation of the operator, and the presence of "logical units" indicates the presence of errors in its actions. The model is used to predict the reliability level of an external pilot of a remotely piloted system. The primary data required to fill it is collected during the testing of the applicant for the post of external pilot under a special program on a special simulator. Simple ratios were obtained to calculate the probability of error-free operation of the pilot, the coefficient of his readiness or unpreparedness, the probability of making the wrong decision in the remote control of the object.